THE INFLUENCE OF THE SAPTA PESONA PROGRAM AND FACILITIES ON THE LEVELS OF TOURIST VISITS AT DOKAN CULTURAL TOURISM OBJECTS - Dinda Sylvia br Sembiring; Edi Winata (Jurnal Ekonomi, 2023)
Study This discusses level visits. This is based on an interview briefly done with visitors' Culture Doc. Study This show exists indication level visit to seven charms and facilities provided. Problem-based observation interview addressed briefly to the visitor. There are levels of dissatisfaction with Sevens The charm and facilities provided. Objective thorough from study This is To determine if seven Power attractions (X1) and facilities (X2) have an impact on visitor volume (Y). As tool data analysis, a multiple linear regression model was used in the methodology descriptive quantitative study. A total of 67 visitors accept the next questionnaire processed with SPSS software. R2 test, t-test, and f test were used For test hypothesis study in a manner statistics. Investigation results in This show that Good Sevens Charm nor facility give influence in a manner simultaneous to the visitor. Based on the partial test also found that there is an influence positive between seven charms and level visits, but at facility No There is an influence to the level indicated visit with results count negative. Whereas magnitude influence between seven charms and amenities to level visit by 45%.